Gene length matters in neurons - Zylka, Mark J. (Neuron, 2015)
A recent study by Gabel et al. (2015) found that Mecp2, the gene mutated in Rett syndrome, represses long (>100 kb) genes associated with neuronal physiology and connectivity by binding to methylated CA sites in DNA. This study adds to a growing body of literature implicating gene length and transcriptional mechanisms in neurodevelopmental and neurodegenerative disorders.